Internal pH and Acid Anion Accumulation in Listeria monocytogenes and Escherichia coli Exposed to Lactic or Acetic Acids at Mildly Acidic pH - Branson, Savannah R.; Broadbent, Jeff R.; Carpenter, Charles E. (Frontiers in Microbiology, 2022)
Organic acids are widely employed in the food industry to control growth of microbial pathogens such as Listeria monocytogenes and Escherichia coli. There is substantial evidence that intracellular accumulation of acid anions is a major inhibitor to cell viability, and that some bacteria are able to combat the toxic effects of anion accumulation via their ability to continue active metabolism at a lower intracellular pH (pHi). This study followed the accumulation of acid anion into the cell pellet and parallel changes in pHi in two human pathogenic strains of L. monocytogenes (N1-227 and R2-499) and in E. coli O157:H7 after exposure to sub-bacteriostatic levels of lactic and acetic acids at mildly acidic pH 6. The methodology employed in these studies included independent measures of pHi and intracellular anion accumulation. For the latter work, cells were pelleted through bromododecane to strip off extracellular water and solutes. Listeria strains accumulated 1.5-fold acetate or 2.5-fold lactate as compared to the external environment while mounting a defense against anion accumulation that included up to a 1-unit pHi drop from 7.5 to 6.5 for strain R2-499. E. coli accumulated 2.5-fold acetate but not lactate and apparently made use of combat mechanisms other than lowering pHi not explored in this study. Inulin was employed to estimate the fractional volume of cell pellet present as intracellular space. That intracellular fraction was 0.24 for E. coli, which infers that acid accumulation into the intercellular space was minimally 4 × that measured for the entire pellet. An intercellular fraction of pellet was not measurable for strains of L. monocytogenes. The data also bring into question the efficacy across bacterial species of the common, but confounding, practice of using intracellular anion accumulation as a measure of pHi, and vice versa.